2020
DOI: 10.3390/molecules25184172
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Pregabalin and Curcumin Synergistically Decreases Pain-Like Behaviors in Acute Nociceptive Pain Murine Models

Abstract: Analgesic drugs in a combination-form can achieve greater efficacy with lesser side effects compared to either drug alone. The combination of drugs acting at different targets or mechanisms of action has been recognized as an alternative approach for achieving optimal analgesia. In this study, the analgesic effects of pregabalin (30, 60, 100, 200 mg/kg), curcumin (15, 30, 60, 100, 120 mg/kg), and 1:1 fixed-dose ratio of the pregabalin-curcumin combination were assessed using two acute nociceptive pain models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…3a). By contrast, the positive control pregabalin (60 mg/kg [23,27]), significantly ameliorated the mechanical hypersensitivity, confirming that the SNI-induced neuropathic pain behavior is responsive to standard analgesic treatment. We then investigated whether capadenoson treatment may inhibit chemotherapy-induced neuropathic pain in the paclitaxel model.…”
Section: Cellular Distribution Of Adenosine a 1 Receptors In Dorsal Root Ganglia And The Spinal Cordmentioning
confidence: 73%
See 1 more Smart Citation
“…3a). By contrast, the positive control pregabalin (60 mg/kg [23,27]), significantly ameliorated the mechanical hypersensitivity, confirming that the SNI-induced neuropathic pain behavior is responsive to standard analgesic treatment. We then investigated whether capadenoson treatment may inhibit chemotherapy-induced neuropathic pain in the paclitaxel model.…”
Section: Cellular Distribution Of Adenosine a 1 Receptors In Dorsal Root Ganglia And The Spinal Cordmentioning
confidence: 73%
“…By contrast, pregabalin, which in this experiment was given at 30 mg/kg p.o. [27], significantly inhibited the mechanical hypersensitivity in comparison to vehicle (Fig. 3c).…”
Section: Sni -Po Delivery Sni -Iv Deliverymentioning
confidence: 79%
“…Several pre-clinical studies have investigated interactions between curcumin and drugs. One such study in mouse models of acute nociceptive pain demonstrated a synergistic interaction in combination with pregabalin [ 61 ]. Curcumin was found to downregulate opioid-related nociceptin receptor 1 gene expression, which codes for nociceptin opioid peptide receptor (NOP), one of the four opioid receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The tail flick method is also broadly applied to assess anti-nociceptive property of compounds. Exposing the tail of mice to heat activates heat sensitive receptors, transient receptor potential vanilloid type 1 and 3 (TRPV1 and TRPV3) receptors promoting pain transmission ( Leksiri et al, 2020 ). Compound 3 exhibited potent analgesic activity in both the tests.…”
Section: Discussionmentioning
confidence: 99%